Recurrence of hepatocellular carcinoma after direct acting antiviral treatment for hepatitis C virus infection: Literature review and risk analysis. Issue 11 (November 2018) - Guarino, Maria; Viganò, Luca; Ponziani, Francesca Romana; Giannini, Edoardo Giovanni; Lai, Quirino; Morisco, Filomena; Vitale, Alessandro; Russo, Francesco Paolo; Cillo, Umberto; Burra, Patrizia; Mescoli, Claudia; et al.
Abstract: Although studies suggest decreased incident hepatocellular carcinoma (HCC) after treatment with direct-acting antivirals (DAAs) for hepatitis C virus (HCV) infection, data are conflicting regarding risk and aggressiveness of recurrence in patients who have a history of treated HCC. This review analyses data available in literature in order to elucidate the impact of DAAs on the risk of HCC recurrence after successful treatment of the tumor. Overall 24 papers were identified. The available data cannot be considered definitive, but the initial alarmist data indicating an increased risk of recurrence have not been confirmed by most subsequent studies. The suggested aggressive pattern (rapid growth and vascular invasion) of tumor recurrence after DAAs still remains to be confirmed. Several limitations of the available studies were highlighted, and should drive future researches. The time-to-recurrence should be computed since the last HCC treatment and results stratified for cirrhosis and sustained viral response. Any comparison with historical series is of limited interest because of a number of biases affecting these studies and differences between enrolled patients. Prospective intention-to-treat analyses will be probably the best contribution to drive clinical practice, provided that a randomized trial can be difficult to design.